The thermodynamic database COST MP0602 for materials for high-temperature lead-free soldering (Journal of Mining and Metallurgy, Section B: Metallurgy, 2012)
The current state of thermodynamic modelling in the field of high-temperature lead-free soldering is presented. A consistent thermodynamic database, containing 18 elements (Ag, Al, Au, Bi, Co, Cu, Ga, Ge, Mg, Ni, P, Pb, Pd, Sb, Sn, Ti and Zn) has been created. The thermodynamic data for the most of the important binary and selected ternary systems were checked and included into the database. The database was tested using major commercial software packages. Such reliable and sophisticated software coupled to reliable thermodynamic databases are necessary prerequisites for application of thermodynamicsin advanced alloys design.